PENGARUH SCHOOL WELL BEING TERHADAP MOTIVASI BELAJAR SISWA - EVA NUR RACHMAH (Personifikasi: Jurnal Ilmu Psikologi, 2017)
This study aims to determine the effect of school well being of the students' motivation. A good education system capable of making prosperous their students. Student welfare important for schools because it is associated with the degree of effectiveness of the communication functions of the students at the school. School well being or welfare of the student in an educational context can not be explained explicitly and in detail as listed in educational policy.Well being Protégé is an order of life and livelihood of the students to ensure the growth and development of the students fairly, both spiritually, physically, and socially.In essence, the motivation to learn is internal and external encouragement to the students who are learn to make changes in behavior.Expected well being a good school can provide a good influence on the students motivation.Result analysis: School well being has a significant effect on learning motivasi.  Keywords: school well being, motivation to learn.